PENGARUH KUALITAS DIMENSI PRODUK TERHADAP KEPUASAN PELANGGAN PADA PRODUK HAFIZ/HAFIZAH TALKING DOLL - Elvi Sunita Perangin-angin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The author conducts quantitative research through the method of distributing questionnaires to 62 respondents. The author uses calculations using SPSS 24.0 in the test of the correlation coefficient and determination, and the regression equation test. Based on the correlation coefficient test it is known that there is a strong relationship between the quality of the product dimension and customer satisfaction with a value of 0.812 (81.2%). Based on the coefficient of determination shows a value of 0.659, meaning that 65.9% of customer satisfaction is influenced by the quality of product dimensions and 34.1% is influenced by other factors. Based on the regression equation test, there is a line equation Y = 6.138 + 0.794 X, which indicates that there is a positive influence between the quality of the product dimension on customer satisfaction so that the quality of the product dimensions must be increased to the maximum extent so that customer satisfaction also increases.